Are Auckland Hospitality Organisations Ready to Maximise Benefits of the Rugby World Cup 2011? - Kang, Brian (Young Rang) (Auckland University of Technology, 2012)
Since the first Rugby World Cup (RWC) was held in 1987, co-hosted by Australia and New Zealand (NZ), it has evolved into the third largest major international sport competition after the Olympics and the Football World Cup. The RWC returned to NZ in September and October 2011 and was expected to generate a wide range of benefits to and opportunities for the country. With matches occurring across the different NZ regions, the economic benefits were expected to be widespread. However, as host of high profile matches including five pool matches, two quarter-finals, both semi-finals, a bronze medal, and the finals match. Auckland was expected to get the most benefits and opportunities from the RWC 2011. Auckland is the research setting for this study. Specifically, the focus is the CBD-to-Mt Eden area, and surrounding areas. Through reviewing existing academic literature on event and hospitality management, it was found that no study had focused on how businesses plan and prepare for a mega-event. This research looks to answer the specific question “how can hospitality organisations prepare for a mega-event to maximise the benefits and opportunities?”. A sequential mixed methods research design was considered the most appropriate technique to answer the research question. The researcher employed interviews (n=14) and a postal questionnaire survey (n=72). The major purpose of this thesis was to investigate, better understand and analyse hospitality organisations’ planning practices for mega-events, through the case of the RWC 2011. Both the qualitative and quantitative research investigated hospitality organisations’ planning practices for the RWC 2011 regarding the marketing mix and human resources management. The research also identified hospitality organisations’ general expectations during and after the RWC 2011, their opinions on the potential external environmental factors, as well as difficulties or challenges they may have in their planning. The findings in the qualitative research section provided a comprehensive understanding and enhanced the general knowledge of the research context by collecting rich descriptive data. Further, the qualitative research phase facilitated the design of the questionnaire for the quantitative research stage. The quantitative research collected statistically reliable, valid and accurate data from the large sample size to represent the target population in the study areas. The standardised data and the Mann-Whitney U test allowed the researcher to compare and identify differences in the planning practices between the food and beverage and accommodation sector. This thesis identified that the majority of the research participants expected the RWC 2011 would increase the numbers of both international and domestic guests, thus generating more revenues during the RWC 2011. There was a smaller number of participants who expected the same benefits after the event. However, a number of participants expected to improve their business reputation and/or awareness after the RWC 2011. There was a significant difference in the pricing decisions between the food and beverage and accommodation sector. Due to the demand and seasonality, accommodation organisations had relatively more flexibility to increase their room rates to maximise revenues. The RWC 2011 had potential to generate employment opportunities as most of the participants sought to recruit additional employees. However, the respondents noted opportunities were less likely to be carried on after the event. Despite a number of participants being aware of the potential benefits and significance of training programmes, they tended to provide training for only new staff members. Only a small number of research participants considered the product and promotion mix as parts of their planning for the RWC 2011. It was further identified that most of the participants paid very little attention or lacked information or knowledge on the external environmental issues. Surprisingly, the majority of the participants did not seek any information or advice for their planning and they did not have any difficulties in the preparation for the RWC 2011. The RWC 2011 was generally perceived as a short-term profit generator and the participants tended to operate their businesses as usual. There will be more favourable post-event outcomes to hospitality organisations, if they view a mega-event as a long-term opportunity to showcase their products and ability to deliver high quality of service by using appropriate approaches.
Keywords: Mega-event; Hospitality; Rugby World Cup; Event Planning; Preparation; Marketing; Human Resources Management